Love Theater: Uhåndgribelige konflikter - Kristensen, Jeppe (Peripeti, 2022)
Love Theater. Uhåndgribelige konflikter by Jeppe Kristensen. Kristensen went to Bangkok to cast a prostitute who should play the leading character in Love Theater. The performance was based on her own life-experiences as prostitute, and the article is reflecting on intangible conflicts, regarding the prejudices of an audience.